A helyi hatalom és a lakossági részvétel esélyei - Bőhm, Antal (Tér és Társadalom, 1987)
The author examines the functioning of loval government in the context of workplace – residence and centre – locality and states that thé centre and workplace have become predominant as a result of the specifically retarded social development in East Europe. This development took place under a similarly traditional, paternalist government which permeated both the politics of the central power and the labour organizations. The Socialist transformation of the country raised hopes for radical changes in this field but industrialization and urbanization programmes in the 1950s strengthened the central power and increased the role of the workplace. The role of the locality and residence was inevitably pushed into the background. Changes in this situation were only brought by the reform programmes of the 1960s, primarily within the enterprises where paternalist management carne to be replaced by modern methods of business organization. Changes in the relationship between centre and locality came, however, with a certain time lag as this issue has only recently been discovered as an important, so far neglected area of socialist democratization. The changes also had an impact on several fields of settlement development, contributed to the recognition of the need for a more equitalbe distribution and the irnportance of population participation. It is still an open question to what extent the local government can meet the increased demands in the present conditions for functioning and through increased participation of the population. At present, local power operates in a onechannel system, with the complete absence of partnership between the centre and the locality. As to the participation of the population, it means nothing more than taking part in voluntary work for the settlement/residential area, considering that the forms and ways of participation of a higher quality have not taken shape yet. As a result of paternalist traditions citizens prefer to wait for central decisions. In this situation it is important to find out if the population is willing, or able to co-operate, if they find it worthwhile taking part in the preparation of local decisions. In this respect there are two tendencies taking shape now; an increased demand for participation, on the one hand, and, on the other, there are still important social groups that choose to keep away from local public lile. Further reform can only bring good results if locality, the place of residence can function as a „school" preparing individuals for a democratic public life.